Kelancaran Lalu Lintas di Kota Padangsidimpuan di Perspektif Fiqh Siyasah - Justika Justika; Khoiruddin Manahan Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study discusses the role of the Padangsidimpuan City Transportation Service in Implementing Article 23 Paragraph 1 of Law Number 22 Year 2009 concerning Traffic Smoothness and Road Transportation. The background of this research is to analyze the role of the Padangsidimpuan City Transportation Service in Implementing Article 23 Paragraph 1 of Law No. 22 of 2009 concerning Traffic Smoothness and Road Transportation, as well as to find out the factors that the Transportation Office does in controlling traffic in Padangsidimpuan City when viewed from the perspective of the Department of Transportation. siyasa fiqh.This research was conducted from October 2021 to March 2022, located in Padang Matinggi, Simpang Silandit, Tugu Siborang, and Sadabuan. This research is a type of field research using qualitative methods (field research) to collect data in the field to obtain accurate information regarding the object under study. Collecting data in this study are interviews, observations or observations, and documentation. The parties studied are the Department of Transportation, Riders, Passengers, and the Community.The results showed that the implementation of Law No. 22 of 2009 article 23 paragraph 1 in the City of Padangsidimpuan concerning the Role of the Department of Transportation in Controlling the Smoothness of Traffic and Road Transportation has not been carried out optimally because of people's habits who do not obey the applicable regulations and do not consider it important to have the rule of law. The inhibiting factors for the implementation of Law Number 22 of 2009 Article 23 Paragraph 1 concerning the Role of the Department of Transportation in Controlling the Smoothness of Traffic and road transportation in the city of Padangsidimpuan are the lack of public awareness about the law, inadequate facilities such as traffic lights, road signs. traffic signs, lack of socialization to the community and lack of quality on the highway.